A Simple Strategy for the Sterile Use of Reusable Laryngoscope Blades in Resource Limited Countries - Mahmoodpoor, Ata; Soleimanpour, Hassan (Annals of Anesthesiology and Critical Care, 2016)
The laryngoscope blade has a potential role for cross infection due to its contamination with bacteria, blood, and microorganisms. Cleaning the laryngoscope blade has various methods in different countries. Most operating rooms have no guidelines for laryngoscope disinfection after each usage (1). Some use tap water for cleaning which is an inadequate method while others add disinfectant to tap water which is more effective for the control of infection, but this may result in the emergence of resistant bacteria. There are so many disinfectants like aldehyde-free biguanide and Chlorine dioxide or chlorhexidine without any international guideline for common practice. Cleaning with most of these disinfectants is time consuming and needs at least 10 minutes for disinfection (2). In some centers, anesthesiologists use disposable blade laryngoscopes which brings, sometimes, difficulty in airway management especially in the emergency situations compared to standard laryngoscopes, because of the shape of the blade or light carrying capacity. Most of the single-use laryngoscopes tested were significantly inferior to the standard Macintosh blade. This raises concern over their use in clinical practice, particularly if intubation is difficult (3). The cost of disposable blades for laryngoscopes is almost 5 to 10 dollars.